Mathematical model of biohydrogen production in microbial electrolysis cell: A review - Mohd Asrul, Mohamad Afiq; Atan, Mohd Farid; Abdul Halim Yun, Hafizah; Lai, Josephine Chang Hui (International journal of hydrogen energy, 2021)
Microbial electrolysis cell (MEC) is a promising reactor. However, currently, the reactor cannot be adapted for industrial-scale biohydrogen production. Nevertheless, this drawback can be overcome by modeling studies based on mathematical equations. The limitation of analytical instrumentation to record the non-linearity of the dynamic behavior for biohydrogen processes in an MEC has led to the introduction of computational approach that has the potential to reduce time constraints and optimize experimental costs. Reviews of comparative studies on bioelectrochemical models are widely reported, but there is less emphasis on the MEC model. Therefore, in this paper, a comprehensive review of the MEC mathematical model will be further discussed. The classification of the model with respect to the assumptions, model improvement, and extensive studies based on the model application will be critically analyzed to establish a methodology algorithm flow chart as a guideline for future implementation. [Display omitted] •Advancement of MEC mathematical models.•Classification of MEC mathematical models.•Proposed guideline for the MEC mathematical model implementation.